A monolithic 3D‐0D coupled closed‐loop model of the heart and the vascular system: Experiment‐based parameter estimation for patient‐specific cardiac mechanics. (16th February 2017) - Hirschvogel, Marc; Bassilious, Marina; Jagschies, Lasse; Wildhirt, Stephen M.; Gee, Michael W.
Abstract: A model for patient‐specific cardiac mechanics simulation is introduced, incorporating a 3‐dimensional finite element model of the ventricular part of the heart, which is coupled to a reduced‐order 0‐dimensional closed‐loop vascular system, heart valve, and atrial chamber model. The ventricles are modeled by a nonlinear orthotropic passive material law. The electrical activation is mimicked by a prescribed parameterized active stress acting along a generic muscle fiber orientation. Our activation function is constructed such that the start of ventricular contraction and relaxation as well as the active stress curve's slope are parameterized. The imaging‐based patient‐specific ventricular model is prestressed to low end‐diastolic pressure to account for the imaged, stressed configuration. Visco‐elastic Robin boundary conditions are applied to the heart base and the epicardium to account for the embedding surrounding. We treat the 3D solid‐0D fluid interaction as a strongly coupled monolithic problem, which is consistently linearized with respect to 3D solid and 0D fluid model variables to allow for a Newton‐type solution procedure. The resulting coupled linear system of equations is solved iteratively in every Newton step using 2 × 2 physics‐based block preconditioning. Furthermore, we present novel efficient strategies for calibrating active contractile and vascular resistance parameters to experimental left ventricular pressure and stroke volume data gained in porcine experiments. Two exemplary states of cardiovascular condition are considered, namely, after application of vasodilatory beta blockers (BETA) and after injection of vasoconstrictive phenylephrine (PHEN). The parameter calibration to the specific individual and cardiovascular state at hand is performed using a 2‐stage nonlinear multilevel method that uses a low‐fidelity heart model to compute a parameter correction for the high‐fidelity model optimization problem. We discuss 2 different low‐fidelity model choices with respect to their ability to augment the parameter optimization. Because the periodic state conditions on the model (active stress, vascular pressures, and fluxes) are a priori unknown and also dependent on the parameters to be calibrated (and vice versa), we perform parameter calibration and periodic state condition estimation simultaneously. After a couple of heart beats, the calibration algorithm converges to a settled, periodic state because of conservation of blood volume within the closed‐loop circulatory system. The proposed model and multilevel calibration method are cost‐efficient and allow for an efficient determination of a patient‐specific in silico heart model that reproduces physiological observations very well. Such an individual and state accurate model is an important predictive tool in intervention planning, assist device engineering and other medical applications. Abstract : We present a model for patient‐specific cardiac mechanics, incorporating a 3D finite element ventricular model coupled to a reduced‐order 0D closed‐loop vascular system, heart valve, and atrial chamber model. The coupled problem is consistently linearized with respect to 3D structural and 0D vascular unknowns and iteratively solved in one monolithic Newton iteration using physics‐based block preconditioning. Efficient strategies for calibrating active contractile and vascular resistance parameters to experimental data gained in porcine experiments are presented, proposing a novel 2‐level nonlinear optimization procedure.